Pemberdayaan Masyarakat dalam Budidaya dan Pemanfaatan Maggot Lalat Tentara Hitam - Nova Hariani; Eko Kusumawati; Retno Aryani; Sus Trimurti; Lariman (Jurnal Pemberdayaan Masyarakat, 2022)
After 2 years of pandemic which caused by corona virus and followed by Restrictions Towards Community Activities (PPKM) was issued by government, has caused negative impact on various sector of community life. The impact on economic sector of society was quite large. Hence, community economic wheels which disrupted by laid off / stay home policy, needs to be maintained by offering home business with low budget. One of community empowerment efforts that can be introduced to society is utilization of household waste / small scale / fresh market to keep maggot black soldier fly (BSF). This maggot BSF is kind of clean fly and not classified as disease vector, otherwise it has many benefits as chicken feed, fish feed, substitution for protein feed, bird feed etc. Maggot has become alternative protein as animal feed. After the participant satisfaction test was held, we got participant satisfaction average values, ranged from very good (rated as 5) 60.2 %, good (rated as 4) 38.6%, and fair (rated as 3) 1.2 %. Overall, all participants were greatly satisfied with our presentation about mentioned knowledge and technology.